2015
DOI: 10.1016/j.brainres.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Distinct morphological processing of recently learned compound words: An ERP study

Abstract: EEG Morphology N400Overt speech Priming a b s t r a c t Our vocabulary is, at least in principle, infinite. We can create new words combining existing ones in meaningful ways to form new linguistic expressions. The present study investigated the morphological processing of novel compound words in overt speech production. Native speakers of Dutch learned a series of new compounds (e.g. appelgezicht, 'apple-face') that were later used as primes in a morphological priming task. In this protocol, primes were compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…First, perceptual conflicts between externally given solutions (strokes) and internally generated ideas (radicals) will certainly lead to semantic conflicts because the radicals convey phonological and semantic information of characters (Zou et al, 2019). Although the classical N400 component tends to have a centroparietal scalp distribution (Lau et al, 2014), it is sensitive to semantic violations in appreciating novel words (Bakker et al, 2015), novel compound words (Kaczer et al, 2015), novel associations (Lin & Yang, 2014), and novel metaphors (Obert et al, 2018). Second, Chinese characters are typical hieroglyphs, and compared with radical‐level decomposition, stroke‐level decomposition breaks the orthographic rules of characters to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…First, perceptual conflicts between externally given solutions (strokes) and internally generated ideas (radicals) will certainly lead to semantic conflicts because the radicals convey phonological and semantic information of characters (Zou et al, 2019). Although the classical N400 component tends to have a centroparietal scalp distribution (Lau et al, 2014), it is sensitive to semantic violations in appreciating novel words (Bakker et al, 2015), novel compound words (Kaczer et al, 2015), novel associations (Lin & Yang, 2014), and novel metaphors (Obert et al, 2018). Second, Chinese characters are typical hieroglyphs, and compared with radical‐level decomposition, stroke‐level decomposition breaks the orthographic rules of characters to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes, Kolinsky, and Ventura (2009) found evidence for lexical integration of word-forms in the context of artificial language learning immediately after training. Besides, Kaczer et al, (2015) found morphological priming for recently learned compound words. In the same vein, De Diego Balaguer et al (2007) found evidence for ERP changes in a word and rule learning experiment after only a four-minute exposure to an artificial language.…”
Section: Introductionmentioning
confidence: 91%
“…In a recent review, Leminen et al ( 2019 ) analyzed more than 100 neuroimaging studies of inflected words (e.g., walk-ed), derived words (e.g., dark-ness), and compounds (e.g., walk-man). As they summarized, most studies of the processing of derivational/inflectional morphology agree that such complex words are decomposed during processing; but studies of the processing of compound words show inconsistent results: some support the access of constituent morpheme units (Koester and Schiller, 2011 ; Fiorentino et al, 2014 ), some support the access of whole-word units (Stites et al, 2016 ), and some support mixed access of both (MacGregor and Shtyrov, 2013 ; Kaczer et al, 2015 ; Yang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%